B-Cells and Antibodies as Contributors to Effector Immune Responses in Tuberculosis - Rijnink, Willemijn F.; Ottenhoff, Tom H.M.; Joosten, Simone A. (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is still a major threat to mankind, urgently requiring improved vaccination and therapeutic strategies to reduce TB-disease burden. Most present vaccination strategies mainly aim to induce cell-mediated immunity (CMI), yet a series of independent studies has shown that B-cells and antibodies (Abs) may contribute significantly to reduce the mycobacterial burden. Although early studies using B-cell knock out animals did not support a major role for B-cells, more recent studies have provided new evidence that B-cells and Abs can contribute significantly to host defense against Mtb. B-cells and Abs exist in many different functional subsets, each equipped with unique functional properties. In this review, we will summarize current evidence on the contribution of B-cells and Abs to immunity towards Mtb, their potential utility as biomarkers, and their functional contribution to Mtb control.